Discover water (Springer Nature Switzerland, 2021)
"Research from across all fields relevant to water - not only as a resource, but also the impact of society on water".
Keywords: Water : Periodicals; Hydrology : Periodicals; Water conservation : Periodicals; Eau : Périodiques; Water